2013
DOI: 10.1186/1479-5876-11-231
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck irradiation modulates pharmacokinetics of 5-fluorouracil and cisplatin

Abstract: Background5-fluorouracil (5-FU) and cisplatin (CDDP) are used to enhance radiotherapy (RT) effect for head and neck (HN) cancers. However, the effect of local RT on systemic chemotherapeutics remains unclear. Here, we evaluated the influence of HN irradiation on the pharmacokinetics (PK) of 5-FU and CDDP in rats as experimental model.MethodsThe radiation dose distributions of HN cancer patients were determined for the low dose areas, which are generously deposited around the target volume. Two Gy and 0.5 Gy RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…To optimize the analytical system, the pH value of the buffer system must be determined. Previous studies showed that a reverse-phase C18 column with the mobile phase of 1% methanol and 99% of 10 mM KH 2 PO 4 (v/v) produces acceptable separation of 5-FU in plasma [ 23 , 24 ]. However, 5-FU plasma samples were collected by withdrawing from the jugular vein, not microdialysis system.…”
Section: Resultsmentioning
confidence: 99%
“…To optimize the analytical system, the pH value of the buffer system must be determined. Previous studies showed that a reverse-phase C18 column with the mobile phase of 1% methanol and 99% of 10 mM KH 2 PO 4 (v/v) produces acceptable separation of 5-FU in plasma [ 23 , 24 ]. However, 5-FU plasma samples were collected by withdrawing from the jugular vein, not microdialysis system.…”
Section: Resultsmentioning
confidence: 99%
“…33 Cisplatin and 5-FU are the two most commonly used chemotherapy agents in head and neck CCRT regimens. 34 Because no rodent models of head and neck CCRT have been reported, a human cisplatin and 5-FU CCRT regimen for advanced head and neck cancers was adapted and optimized in the current study. [18][19][20] Our model was designed to capture both acute and subacute/chronic changes in tongue function and structure following BOT CCRT.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence shows that irradiation may not only has DNA damage effects but also sends signals to their neighborhood, the so-called as bystander effect [ 10 , 11 ] or longer-range effects such as the abscopal effects [ 12 ]. Our recent studies reported that local RT could modulate the systemic pharmacokinetics (PK) of 5-FU with different RT doses in an experimental rat model [ 13 , 14 ] through matrix metalloproteinase-8 (MMP-8) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%